FLUKA Monte Carlo for Basic Dosimetric Studies of Dual Energy Medical Linear Accelerator. (24th July 2014) - Abdul Haneefa, K.; Cyriac, T. Siji; Musthafa, M. M.; Ganapathi Raman, R.; Hridya, V. T.; Siddhartha, A.; Shakir, K. K.
Abstract : General purpose Monte Carlo code for simulation of particle transport is used to study the basic dosimetric parameters like percentage depth dose and dose profiles and compared with the experimental measurements from commercial dual energy medical linear accelerator. Varian Clinac iX medical linear accelerator with dual energy photon beams (6 and 15 MV) is simulated using FLUKA. FLAIR is used to visualize and edit the geometry. Experimental measurements are taken for 100 cm source-to-surface (SSD) in 50 × 50 × 50 cm 3 PTW water phantom using 0.12 cc cylindrical ionization chamber. Percentage depth dose for standard square field sizes and dose profiles for various depths are studied in detail. The analysis was carried out using ROOT (a DATA analysis frame work developed at CERN) system. Simulation result shows good agreement in percentage depth dose and beam profiles with the experimental measurements for Varian Clinac iX dual energy medical linear accelerator.